The Shifting of Marketing Strategy During Pandemic Covid-19: Case Study on PT Summarecon Bekasi - Ikhsan Nugraha; Eko Sakapurnama (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2021)
Abstract. As we know that Covid-19 become the biggest challenge for corporation to perform its business. This study aims to explain the shifting in implementing marketing strategy through social media marketing activities, electronic word of mouth and brand equity and measure the purchase intention of PT Summarecon Bekasi’s followers. The study uses a quantitative approach through survey methods based on purposive and snowball sampling of the population. The number of respondents in this study were 175 of Summarecon Instagram followers that obtained through an online questionnaire. The data obtained were processed using SPSS through descriptive statistical analysis and multiple regression. The results of this study indicate that the relationships held in the research model are significant and mutually influential toward dependent variable. Overall, PT Summarecon Bekasi is expected to upgrade its marketing content through social media which is more interesting to gain purchase intention of consumers towards Summarecon Bekasi property.Keywords: Social Media Marketing Activities, Electronic Word of Mouth, Brand Equity, Purchase Intention